Assessment of the Effectiveness of Silver-Coated Dressing, Chlorhexidine Acetate (0.5%), Citric Acid (3%), and Silver Sulfadiazine (1%) for Topical Antibacterial Effects Against the Multi-Drug Resistant Pseudomonas Aeruginosa Infecting Full-Skin Thickness Burn Wounds on Rats - Yabanoglu, Hakan (The International College of Surgeons, World Federation of General Surgeons and Surgical Specialists, Inc., 2013)
The aim of this study was to compare the effects of four different topical antimicrobial dressings on a multi-drug resistant Pseudomonas aeruginosa contaminated full-thickness burn wound rat model. A total of 40 adult male Wistar albino rats were used. The control group (group 1), silver sulfadiazine (1%) group 2, chlorhexidine acetate (0.5%) group 3, citric acid (3%) group 4, and silver-coated dressing group 5 were compared to assess the antibacterial effects of a daily application to a 30% full-skin thickness burn wound seeded 10 minutes earlier with 10(8) CFU (colony forming unit)/0.5 mL of a multi-drug resistant Pseudomonas aeruginosa strain. Five groups (1 control group and 4 treatment groups) were compared. The administration of third-degree burns to all rats was confirmed based on histopathologic data. The tissue cultures from groups 2 and 5 exhibited significant differences compared to those of the other 3 groups, whereas no significant differences were observed between groups 1, 3, and 4. The effectiveness of the treatments was as follows: 1% silver sulfadiazine > silver-coated dressing > 3% citric acid > 0.5% chlorhexidine acetate > control group. Our results supported the efficacy of topical therapy by silver sulfadiazine and silver-coated dressing on infections caused by multi-drug resistant Pseudomonas spp.